MYOPATHY AND PARKINSONISM IN PHOSPHOGLYCERATE KINASE DEFICIENCY - SOTIRIOU, EVANGELIA (Muscle Nerve, 2010)
A 25-year-old man with exertional myoglobinuria had no evidence of hemolytic anemia, but he had severe parkinsonism that was responsive to levodopa. Phosphoglycerate kinase (PGK) activity was markedly decreased in muscle, and molecular analysis of the PGK1 gene identified the p.T378P mutation that was recently reported in a patient with isolated myopathy. This case reinforces the concept that PGK deficiency is a clinically heterogeneous disorder and raises the question of a relationship between PGK deficiency and idiopathic juvenile Parkinson disease.